Premature and Early Menopause in Relation to Cardiovascular Disease - Schipper, Izaäk; Louwers, Yvonne V. (Seminars in Reproductive Medicine, 2020)
Postmenopausal women have an increased risk for cardiovascular diseases. It has been postulated that the loss of ovarian function and subsequent deficiency of endogenous estrogens after menopause contributes to this elevated risk of cardiovascular disease in postmenopausal women. Compared with woman entering menopause at the mean age of 51 years, in women with early menopause or premature ovarian insufficiency the risk for cardiovascular disease is even greater. These women lack the cardioprotective effect of endogenous estrogens for many more years than do women entering natural menopause. The majority of data assessing the risk of cardiovascular disease in relation to age at menopause and specifically premature menopause are derived from large epidemiological cohort studies. In addition, observations in women undergoing bilateral oophorectomy at an early age provide convincing evidence regarding association between early menopause or POI and the development of cardiovascular events and mortality. Moreover, genetic variants associated with earlier age at menopause have also been found to increase the risk of cardiovascular events in women. It has been substantiated that hormone replacement therapy (HRT) decreases the risk for ischemic heart disease and eliminates the increased cardiovascular disease mortality. It is therefore crucial to start HRT as soon as possible, particularly in women with premature ovarian insufficiency.
Keywords: early menopause; premature ovarian insufficiency; cardiovascular disease; mortality; hormone replacement therapy